STRENGTHENING RELIGIOUS CHARACTER THROUGH RELIGIOUS EXTRACURRICULAR ACTIVITIES IN ISLAMIC BOARDING SCHOOL EDUCATIONAL INSTITUTION - Nor Alim Kilmi; Moh. Jasri; Hilya Banati Hajriyah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This stu dy aims to identify the strengthening of students' religious character through religious extracurricular activities at SMA Al-Fattah Sukosari, Bondowoso. Religious character plays a crucial role in shaping students' personalities, which can be reinforced through religious activities outside formal lessons. This research uses a qualitative approach with a descriptive method. Data were collected through observation, interviews with guidance teachers and students, and documentation related to the religious extracurricular programs at the school. The results show that religious extracurricular activities such as religious study sessions, book studies, Quran memorization training, and joint worship have a significant role in shaping students' religious character. These activities help students understand and internalize religious values, which lead to improvements in discipline, responsibility, and mutual respect among peers. Furthermore, the strengthening of religious character is also influenced by the active role of teachers who guide and motivate students. Parental support is also an important factor in reinforcing the religious values taught at school. This study concludes that the religious extracurricular activities at SMA Al-Fattah Sukosari are effective in cultivating students' religious character. Therefore, the development and improvement of the quality of religious extracurricular activities are highly recommended to achieve more optimal results in shaping students who are not only intellectually intelligent but also possess noble character and religious values.